Herbal Therapy on Fasting Blood Glucose Levels and HbA1c in Type 2 Diabetes Mellitus Patients: A Systematic Review - Dinatha, I Dewa Putu Narendra; Tarigan, Abraham Mulia; Irawan, Putu Ferdi; Raya, Nyoman Agus Jagat (Faculty of Nursing, Universitas Hasanuddin, 2025)
Aims: To investigate the effectiveness of herbal extracts in reducing Fasting Blood Glucose (FBS) and HbA1c levels in patients with type 2 Diabetes Mellitus (T2DM) and identify gaps in evidence-based practice for the use of herbal therapies in T2DM management. Methods: A literature search was conducted across three major databases: ProQuest, PubMed, and Google Scholar, using specific keywords combined with Boolean logic (“AND” and “OR”) to enhance search precision. The quality of the studies was assessed using the JBI Critical Appraisal tool and ROB 2.0, which evaluate the risk of bias across five domains. Eight studies that met the inclusion criteria were systematically analyzed. Results: The analysis revealed three main themes: (1) a decrease in FBS, (2) a decrease in both FBS and HbA1c, and (3) no significant decrease in either parameter. Certain herbal extracts, such as Bauhinia forficata, barberries, a combination of berries and fenugreek, and Jinlida have been shown to significantly reduce FBS and HbA1c levels. Conclusions: The findings of this study provide valuable insights into the potential use of herbal extracts as complementary therapies for T2DM. These results may contribute to the development of evidence-based nursing practices for the use of herbal treatments in T2DM care.